2020
DOI: 10.1101/2020.05.26.117309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuronal resonance can be generated independently at distinct levels of organization

Abstract: Neuronal resonance is defined as maximal amplification of the response of a system to a periodic input at a finite non-zero input frequency band. Resonance has been observed experimentally in the nervous system at the level of membrane potentials, spike times, post-synaptic potentials, and neuronal networks. It is often assumed that resonance at one level of organization endows resonance at another level, but how the various forms of neuronal resonances interact is unknown. Here we show that a direct link of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Electrical resonance occurs when a system ( e.g. , a neural cell) oscillates with greater amplitude at a specific frequency [47] . It has been demonstrated that these oscillatory signals can influence connectivity between neurons, synaptic communication, and the rhythm of spike firing [48] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical resonance occurs when a system ( e.g. , a neural cell) oscillates with greater amplitude at a specific frequency [47] . It has been demonstrated that these oscillatory signals can influence connectivity between neurons, synaptic communication, and the rhythm of spike firing [48] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that these oscillatory signals can influence connectivity between neurons, synaptic communication, and the rhythm of spike firing [48] . For mammalian neurons, the resonance frequency has been observed to range from 4 to 10 Hz [47] . The final optimal PRF range found in this study is reasonably consistent with the mammals' resonance frequency range.…”
Section: Discussionmentioning
confidence: 99%